Situational diagnosis of policies in Latin American and Caribbean countries for the use of fluoride and reduction of sugar consumption - Saul Martins PAIVA; Ivana Meyer PRADO; Matheus França PERAZZO; Carol C. GUARNIZO-HERREÑO; Ana Maria ACEVEDO; Jorge Luis CASTILLO; Ninoska ABREU-PLACERES; Rodrigo Andrés GIACAMAN; Antônio Pedro RICOMINI-FILHO; Stefania MARTIGNON; Zilson MALHEIROS; Bernal STEWART; et al. (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract Policy evaluation and guidance on fluoride use and sugar consumption in Latin American and Caribbean countries (LACC) may provide a scientific evidence basis for policymakers, dental professionals, civil society organizations and individuals committed to improving public oral health. A cross-sectional study was conducted to evaluate the extent of implementation of policies/guidelines on fluoride use, and sugar consumption in LACC. The study had two stages. First a questionnaire covering four major areas was developed: fluoridation of public water supplies; salt fluoridation; fluoride dentifrices, and sugar consumption. Then, the questionnaire was applied to collect data among representative participants in public oral health from LACC. Ninety-six participants from 18 LACC answered the questionnaire. One-hundred seventy documents were attached, and 285 links of websites were provided by the respondents. Implementation of policies and guidelines on water and table salt fluoridation and processed and ultra-processed food consumption were found in most countries, with some issues in the consensus and coverage. Thus, differences were identified in the extent of implementation of public oral health strategies on sugar consumption and fluoridation among the countries. There is no consensus on the policies in LACC to reduce sugar consumption and for the use of fluoride. A few policies and guidelines were applied in isolated countries, with a variety of strategies and standards. For future actions, it will be important to encourage the development of strategies and public policies within countries, and to evaluate the effectiveness of existing policies in reducing dental caries and in improving oral health in LACC.